Penerapan Konservasi Energi Myra Levine Pasien Acutely Decompensated Heart Failure (ADHF) - Fakrul Ardiansyah; Elly Nurachmah; Muhammad Adam; Nurul Anjarwati; Revani Hardika; Azhari Baedlawi (STIKes MERCUBAKTIJAYA, 2022)
ABSTRACT Cardiovascular system nursing care and Acutely Decompensated Heart Failure (ADHF) cases increase every year accompanied by an increase in life expectancy. Cardiovascular system disorders nursing care with energy conservation theory approach developed by Myra Levine. Patients with cardiovascular disorders on average experience shortness of breath during activities and chest pain. A balance of energy input and output is required to avoid excessive fatigue. The main focus of care is acute cardiac care. The purpose of this case study is to provide nursing care for ADHF patients with Myra Levine's energy conservation theory approach. This research design uses a descriptive case study approach. The sample in this study was a patient diagnosed with Acutely Decompensated Heart Failure (ADHF). The results of the application of nursing care in ADHF patients with Myra Levine's energy conservation theory approach obtained conservation priority Tropichognosis: Activity intolerance; and priority structural integrity: decreased cardiac output. The results of the priority hypothesis of nursing care in ADHF patients with Myra Levine energy conservation theory approach obtained an effective heat pump. The priority intervention applied in nursing care for ADHF patients with Myra Levine’s energy conservation approach is acute cardiac care. The final result of nursing care for ADHF patients with the energy conservation theory approach of Myra Levine, it was found that patients were able to conserve the problem of decreasing cardiac output. Keywords: Acutely Decompensated Heart Failure (ADHF); Myra Levine; energy conservation theory ABSTRAK Asuhan keperawatan sistem kardiovaskuler serta kasus ADHF meningkat setiap tahunnya diiringi dengan peningkatan usia harapan hidup. Asuhan keperawatan gangguan system kardiovaskuler dengan pendekatan teori konservasi energi yang dikembangkan Myra Levine. Pasien yang mengalami gangguan kardiovaskuler rata-rata mengalami keluhan sesak saat beraktivitas dan nyeri dada. Keseimbangan input dan output energi diperlukan untuk menghindari kelelahan berlebihan. Fokus perawatan utama adalah perawatan jantung akut. Tujuan studi kasus ini adalah melakukan asuhan keperawatan pada pasien ADHF dengan pendekatan teori konservasi energi Myra Levine. Desain penelitian ini menggunakan desain deskriptif pendekatan studi kasus. Sampel dalam penelitian ini adalah 1 pasien terdiagnosis Acutely Decompensated Heart Failure (ADHF). Hasil penerapan asuhan keperawatan pada pasien ADHF dengan pendekatan teori konservasi energy Myra Levine didapatkan Tropichognosis prioritas konservasi: Intoleransi aktivitas; dan prioritas integritas structural: penurunan curah jantung. Hasil prioritas hipotesis asuhan keperawatan pada pasien ADHF dengan pendekatan teori konservasi energy myar Levine didapatkan pompa jantung efektif. Intervensi prioritas yang diterapkan dalam asuhan keperawatan pada pasien ADHF dengan pendekatan konservasi energy myra Levine adalah perawatan jantung akut. Hasil akhir asuhan keperawatan pada pasien ADHF dengan pendekatan teori konservasi energy myra Levine didapatkan pasien mampu melakukan konservasi terhadap masalah penurunan curah jantung. Kata Kunci : Acutely Decompensated Heart Failure (ADHF); Myra Levine; Teori Konservasi Energi